Histoplasma var. duboisii in Portugal. African souvenir? - Veríssimo, Cristina (2018)
Objectives: Histoplasmosis is an infection caused by Histoplasma capsulatum. Infections are caused by two varieties: Histoplasma capsulatum var. capsulatum, endemic in North and South America, and Histoplasma capsulatum var. duboisii, endemic in Central and West Africa and Madagascar Island. Variety duboisii has tropism for lymph nodes, skin, and bones, being classically associated with cutaneous lesions. In the last decades, several imported cases of African histoplasmosis have been reported; the majority of them appeared only 40 years after exposure and in soldiers that fought in Portuguese African countries during the sixties. Increase in travelling and migrations contribute to changes in the epidemiological pattern of this infection. Nevertheless, the true burden of African histoplasmosis is not fully known since it is not a notifiable disease. The aim of this work was to review the number of cases of African histoplasmosis reported in Portugal during an 8 year period and raise the attention to the clinical features of this infection and to the importance of including histoplasmosis in the differential diagnosis of infectious diseases. Methods: We retrospectively reviewed cases of African histoplasmosis diagnosed in Portugal at the Mycology National Reference Laboratory and cases published in scientific papers from 2009 to 2017. Published cases were searched using the following search engines: PubMed, and B-on Platform. Collected data included clinical presentation, underlying disease, outcome, age, gender, nationality, country, period of exposure and methodology for the diagnosis. Results Between 2009 and 2016, eight cases of African histoplasmosis were reported, five were localized infections, and whereas three patients presented disseminated infection with multiple lesions, from In this last case, ones two of the patients were children. In all cases except one, patient were male, with a median age of 62 years old. Three patients born in Guinea-Bissau and five have born in Portugal and had been exposed in Guinea-Bissau or Angola long time ago. The median latency period after exposure was 40,.5 years. Culture was positive in 7 out of 8 cases. Histological stains for fungi were performed in 7 cases and narrow large based yeasts were observed in all the cases. Antibody testing was performed in 3 cases and but just only 1 were was positive. Conclusion: Although Histoplasmosis is considered as a rare disease in Portugal, these data should be kept in mind for persons who born in or travelled to Africa, even many years after returning from the disease-endemic area. Underlying immunosuppression is not condition for this infection. Histological stains for fungi and culture are both gold standard for diagnosis. Molecular methods are not commercially available and antibody detection may not be as sensitive for African histoplasmosis as it is for the capsulatum variety. Increased intercontinental travelling raises the risk of acquiring endemic infections like histoplasmosis. Prognosis of the disease depends on early diagnosis and administration of appropriate and well-conducted therapy. Surveillance is mandatory to understand the true burden of the disease.